Treatment of brain metastases in ALK-positive non-small cell lung cancer. (September 2021) - Ceddia, Serena; Codacci-Pisanelli, Giovanni
Graphical abstract: Highlights: Brain metastases are frequent in ALK-positive NSCLC already at diagnosis. Radiation treatment of brain metastases may cause severe toxicities. ALK-inhibitors are active also against brain metastases and in case of asymptomatic lesions may be used upfront. Radiotherapy should be used in large and/or symptomatic metastases and in case of tumour progression. Abstract: Brain metastases are quite frequent in patients with ALK-translocated non-small cell lung cancer (NSCLC): they are often not amenable to surgical resection and are generally treated with radiotherapy (RT). This however causes severe late toxic side effects that may become invalidating considering the relatively long survival provided by recent medical treatment with target therapies. Several clinical trials have demonstrated that ALK-inhibitors (crizotinib, alectinib, brigatinib) show excellent activity also against brain metastases. It is therefore reasonable, in asymptomatic patients, to start treatment with specific inhibitors: RT will be used at the time of tumor progression or when symptoms appear. This sequence provides the best quality of life for patients.